2016
DOI: 10.1038/eye.2016.115
|View full text |Cite
|
Sign up to set email alerts
|

Uveitic macular edema

Abstract: Macular edema (ME) may complicate anterior,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 85 publications
0
65
0
3
Order By: Relevance
“…Uveitic CME is thought to result from increased vascular permeability due to the breakdown of BRB and is a major risk factor for vision loss (Fardeau et al. ; Goldhardt & Rosen ) and often difficult to manage (Androudi et al. ; Fardeau et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uveitic CME is thought to result from increased vascular permeability due to the breakdown of BRB and is a major risk factor for vision loss (Fardeau et al. ; Goldhardt & Rosen ) and often difficult to manage (Androudi et al. ; Fardeau et al.…”
Section: Discussionmentioning
confidence: 99%
“…In Androudi et al (2010), intravitreal adalimumab showed no efficacy in improving BCVA or decreasing CMT; however, it should be noted that in this particular study, all patients had refractory CME at baseline. Uveitic CME is thought to result from increased vascular permeability due to the breakdown of BRB and is a major risk factor for vision loss (Fardeau et al 2015;Goldhardt & Rosen 2016) and often difficult to manage (Androudi et al 2010;Fardeau et al 2015;Deuter et al 2016;Goldhardt & Rosen 2016). As longstanding CME will result in irreversible damage to as a result of outer retinal and photoreceptor damage, anatomical resolution of the CME will not lead to improvement in BCVA (Androudi et al 2010).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…More than 30% patients with uveitis can develop serious sight-threatening vision loss due to UME. [1][2][3] The prevalence of UME is more common with posterior uveitis. However, any form of inflammation in the eye, including anterior uveitis (AU), can lead to UME.…”
mentioning
confidence: 99%
“…Cystoids are fluid accumulation in cyst-like spaces in the outer plexiform layer of the macula. Cystoid Macular Edema (CME) complicates the course of many ocular disorders such as uveitis, diabetic retinopathy, retinal vein occlusion, retinitis pigmentosa, radiation retinopathy and may also complicate intraocular surgery [1,2]. Inflammatory macular edema can occur in anterior, intermediate or posterior uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory macular edema can occur in anterior, intermediate or posterior uveitis. Uveitis can have varied etiologies including infections, tumors, autoimmunity or idiopathic causes [2]. It typically presents as an active, chronic inflammation and may eventually develop an epiretinal membrane.…”
Section: Introductionmentioning
confidence: 99%